2018
DOI: 10.1016/j.foodchem.2018.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and quality parameters of avocado oil obtained by different processes

Abstract: The objective of this study was to evaluate the quality of avocado oil whose pulp was processed through different drying and oil extraction methods. The physicochemical characteristics of avocados cv. Breda were determined after drying the pulp in an oven under ventilation (40 °C and 60 °C) and vacuum oven (60 °C), followed by the oil extracted by mechanical pressing or the Soxhlet method. From the approximately 72% pulp found in the avocado fruit, the 16% fraction is lipids. The quality indices evaluated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
6
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 29 publications
8
64
6
8
Order By: Relevance
“…This observation partially agrees with Kozłowska et al, who stated that the use of a polar solvent during oil extraction able extract a greater amount of phenolic content from the plant materials. Previously, the TPC of mechanically pressed avocado oil and commercial avocado oil were reported to be 46.07–77.36 mg GAE/100 g and 4.26–5.69 mg GAE/100 g, respectively . These values were much lower than the present study.…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…This observation partially agrees with Kozłowska et al, who stated that the use of a polar solvent during oil extraction able extract a greater amount of phenolic content from the plant materials. Previously, the TPC of mechanically pressed avocado oil and commercial avocado oil were reported to be 46.07–77.36 mg GAE/100 g and 4.26–5.69 mg GAE/100 g, respectively . These values were much lower than the present study.…”
Section: Resultscontrasting
confidence: 86%
“…This can be attributed to the good solubility of carotenoids in organic solvents such as hexane, petroleum ether, and ethyl acetate . Krumreich et al reported very much higher of TCC (75.00–104.62 mg β‐carotene/kg) in mechanically pressed avocado oil than the present study. In contrast, Wong et al reported the TCC of cold‐pressed avocado oil was 1.0–3.5 mg kg −1 .…”
Section: Resultscontrasting
confidence: 42%
See 1 more Smart Citation
“…The physicochemical characteristics of oil as well as the bioactive and harmful components are reported in Table to evaluate the oil quality of rapeseed oil extracted by the AAEP with soak‐heating pretreatment. The acidity value and peroxide value of refined rapeseed oil extracted by the AAEP were just 0.05 g kg −1 and 0.92 mmol kg −1 , respectively, which were both lower than that of commercial oils (commercial oil A was produced by pressing, commercial oil B was produced by hexane extraction) and meet the CAC standard . These values are also lower than that reported by Krumreich et al .…”
Section: Resultscontrasting
confidence: 51%
“…Other important fatty acids of avocado fruit, although less abundant, are linoleic (polyunsaturated) and palmitic (saturated) acids . According to the American Dietetic Association (ADA), avocado fruit is classified as a functional food owing to its high nutritional value and proven beneficial effects on human health due to the presence of many bioactive lipid‐soluble components …”
Section: Introductionmentioning
confidence: 99%